Apolipoprotein M overexpression through adeno‐associated virus gene transfer improves insulin secretion and insulin sensitivity in Goto‐Kakizaki rats. Issue 5 (9th May 2020) - Yu, Yang; Zhang, Jun; Yao, Shuang; Pan, Lili; Luo, Guanghua; Xu, Ning
Abstract: Aims/Objective: The development of type 2 diabetes is a result of insulin resistance in various tissues, including skeletal muscle and liver. Apolipoprotein M (ApoM) plays an important role in the function of high‐density lipoprotein, and also affects hepatic lipid and glucose metabolism. In this study, we aimed to investigate whether ApoM overexpression modulates glucose metabolism and improves insulin sensitivity. Materials and Methods: The Goto‐Kakizaki (GK) rats were transfected with adeno‐associated virus (AAV) encoding rat ApoM gene or control blank. The oral glucose tolerance test (OGTT) and hyperinsulinemic‐euglycemic clamp (HEC) experiment were used to assess the insulin sensitivity of GK rats. Results: The results show that ApoM messenger ribonucleic acid and protein were significantly overexpressed in the pancreatic tissues. Overexpression of ApoM decreased fasting blood glucose and random blood glucose, improved glucose tolerance, and increased bodyweight and insulin levels in GK rats. The glucose infusion rate of rats in the AAV encoding rat ApoM gene group during HEC test was 1.04‐, 1.23‐ and 1.95‐fold higher than that in the AAV control blank group at 1–3 weeks after injection of AAV, respectively. A Wes‐ProteinSimple assay and quantification was carried out to assess phosphorylated protein kinase B/protein kinase B protein levels in the muscle tissues of ApoM‐overexpressing GK rats, and they were found to be higher than those of the control group at the seventh week after AAV injection. Conclusions: ApoM overexpression through adeno‐associated virus gene transfer might improve insulin secretion and insulin sensitivity in GK rats. Abstract : Apolipoprotein M overexpression decreased fasting blood glucose and random blood glucose, and increased insulin in Goto‐Kakizaki rats. Apolipoprotein M overexpression increased the phosphorylated protein kinase B/protein kinase B protein levels in the muscle tissues of Goto‐Kakizaki rats. Apolipoprotein M overexpression might improve insulin sensitivity in Goto‐Kakizaki rats.